A cross sectional study to evaluate the knowledge, attitude and practices of healthcare professionals on pharmacovigilance at Silchar medical college and hospital, Assam, India - Thakuria, Nishanta; Deka, Dipjyoti; Choudhury, Devarsi; Ahmed, Nazar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The primary objective of this study is to evaluate the knowledge, attitude and practice (KAP) of the doctors and students at Silchar medical college and hospital, Assam, India. Pharmacovigilance has gained worldwide importance and this study tries to widen its base in the north eastern part of India. The major task of pharmacovigilance programme is to collect and analyse the reports of adverse drug reactions and inform the potential risk. Methods: The study was cross sectional, questionnaire based, designed to assess KAP of pharmacovigilance. 220 participated among whom 100 were post graduate (PG) students of various departments, 60 MBBS students and 60 interns. Results: The difference in knowledge between the post graduates, interns and MBBS students were highly significant, though all of the groups scored in the moderate section. In the practice section, significant difference was found among the groups, but it is alarming to see that the scoring of the MBBS students fell in the poor category. Conclusions: PGs, interns and MBBS students had a good attitude towards pharmacovigilance but knowledge and practice needs improvement. Constant motivation and support through seminars, workshops and adverse drug reporting will remarkably improve this programme.